Global Pension Systems and Their Reform : Worldwide Drivers, Trends, and Challenges - Holzmann, Robert (World Bank, Washington, DC, 2013)
Across the world, pension systems and their reforms are in a constant state of flux driven by shifting objectives, moving reform needs, and a changing enabling environment. The ongoing worldwide financial crisis and the adjustment to an uncertain 'new normal' will make future pension systems different from past ones. The objectives of this policy review paper are threefold: (i) to briefly review recent and ongoing key changes that are triggering reforms; (ii) to outline the main reform trends across pension pillars; and (iii) to identify a few areas on which the pension reform community will need to focus to make a difference. The latter includes: creating solutions after the marginalization or, perhaps, demise of Bismarckian systems in countries with high rates of informality; keeping the elderly in the labor market; and addressing the uncertainty of longevity increases in pension schemes.